ANALISIS KARAKTER ORANG TUA DI FILM TURNING RED GUNA MEMBANTU ORANG TUA DALAM PENGEMBANGAN POLA ASUHNYA TERHADAP PEMBENTUKAN KARAKTER ANAK USIA DINI - Ramadhani, Ambar Putri; Lestari, Widya; Putri, Nia Karmila; Karunia, Karunia; Hayati, Zalmi; Sofyan, Fuaddilah Ali (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
This research is entitled character analysis of parents in the film turning red to help parents in developing their parenting towards early childhood character building. This study aims to describe and analyze the characters of mei-mei parents who are useful for helping parents in developing their parenting patterns for the formation of early childhood characters in the Disney+ animated film